2020
DOI: 10.3389/fphar.2020.00340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Binding on Exposure of Unbound and Total Mycophenolic Acid: A Population Pharmacokinetic Analysis in Chinese Adult Kidney Transplant Recipients

Abstract: AIMS A population pharmacokinetic (PK) analysis was performed to: (1) characterise the PK of unbound and total mycophenolic acid (MPA) and its 7-O-mycophenolic acid glucuronide (MPAG) metabolite, and (2) identify the clinically significant covariates that cause variability in the dose-exposure relationship to facilitate dose optimisation.METHODS A total of 740 unbound MPA (uMPA), 741 total MPA (tMPA) and 734 total MPAG (tMPAG) concentration-time data from 58 Chinese kidney transplant patients were analysed usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…MPA PK has been extensively studied in kidney transplant recipients 22,31,41‐44 . CL MPA /F (9.05 L∙h −1 ) at more than 1 month post‐transplantation and CL MPAG /F (1.09 L∙h −1 ) were similar to previously reported values (9.3–13.6 and 0.96–1.7 L∙h −1 , respectively) 4,22,32,42,44‐46 . We found that CL MPA /F (10.9 L∙h −1 ) within 1 month post‐transplantation was markedly lower than that previously reported 32,47 (17–27 L∙h −1 ), possibly because of the different regimens (cyclosporine or tacrolimus), higher body weight of patients, relatively low serum ALB levels, and ethnic differences, among other factors.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…MPA PK has been extensively studied in kidney transplant recipients 22,31,41‐44 . CL MPA /F (9.05 L∙h −1 ) at more than 1 month post‐transplantation and CL MPAG /F (1.09 L∙h −1 ) were similar to previously reported values (9.3–13.6 and 0.96–1.7 L∙h −1 , respectively) 4,22,32,42,44‐46 . We found that CL MPA /F (10.9 L∙h −1 ) within 1 month post‐transplantation was markedly lower than that previously reported 32,47 (17–27 L∙h −1 ), possibly because of the different regimens (cyclosporine or tacrolimus), higher body weight of patients, relatively low serum ALB levels, and ethnic differences, among other factors.…”
Section: Discussionsupporting
confidence: 84%
“…MPA has a complex pharmacokinetic (PK) profile with great differences 2‐4 . After oral administration, MMF is quickly and completely converted into MPA.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, a series of covariates, including low plasma albumin levels and accumulation of the inactive MPAG, decreased the binding of MPA to ALB. WT and ALB were found to significantly influence MPA clearance and distribution volume or the protein-binding rate in renal transplant recipients (de Winter et al, 2010;Sheng et al, 2020). The subsequent increase in unbound MPA produces an increase in MPA clearance, resulting in decreased MPA exposure (de Winter et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, also other factors may be important, and our study does not provide information on the influence of gastro-intestinal absorption, proton pump inhibitor use, ethnicity, or UGT-enzyme polymorphisms that could possibly have contributed to this variation. MPA exposure is also shown to be affected by plasma albumin concentrations with a risk of increased MPA exposure in patients with low albumin levels ( Sheng et al, 2020 ). However, the limited number of plasma albumin measurements precluded us from including this factor in the regression analysis.…”
Section: Discussionmentioning
confidence: 99%